2012
DOI: 10.1038/nn.3176
|View full text |Cite
|
Sign up to set email alerts
|

Behavior-dependent specialization of identified hippocampal interneurons

Abstract: A large variety of GABAergic interneurons control information processing in hippocampal circuits governing the formation of neuronal representations. Whether distinct hippocampal interneuron types contribute differentially to information-processing during behavior is not known. We employed a novel technique for recording and labeling interneurons and pyramidal cells in drug-free, freely-moving rats. Recorded parvalbumin-expressing basket interneurons innervate somata and proximal pyramidal cell dendrites, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
264
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(284 citation statements)
references
References 49 publications
19
264
1
Order By: Relevance
“…The activity of PV + interneurons in the hippocampus substantially changes during network oscillations, such as theta (4-10 Hz), gamma (40-100 Hz), and ripple activity (140-200 Hz). In the absence of oscillatory activity, action potential frequency is low (6.5 Hz;87). During theta oscillations, action potential frequency markedly increases (21 Hz).…”
Section: Activity Of Pvmentioning
confidence: 99%
“…The activity of PV + interneurons in the hippocampus substantially changes during network oscillations, such as theta (4-10 Hz), gamma (40-100 Hz), and ripple activity (140-200 Hz). In the absence of oscillatory activity, action potential frequency is low (6.5 Hz;87). During theta oscillations, action potential frequency markedly increases (21 Hz).…”
Section: Activity Of Pvmentioning
confidence: 99%
“…Periodic perisomatic inhibition has been held responsible for the generation of the high-frequency components and the phaselocking of neuronal activity [3], but no convincing data are available about the initiation of SWRs, although the SWR state is considered an "off-line" state of the hippocampus [1 2]. To uncover the participation of different types of neurons in SWR generation, several in vivo [28][29][30][31][32][33][34] and in vitro [35][36][37] studies have examined the firing characteristics of identified neuron types (summarized in [38]). Mostly similar relative firing patterns were found for the examined cell types, but there were some contradictory results, which might have arisen from differences between the CA1 and the CA3 area, and most importantly from anaesthetized compared to freely moving animals or in vitro slices.…”
Section: Introductionmentioning
confidence: 99%
“…While it is clear that basket cells inhibit their target neurons, the effect of axo-axonic cells is still debated and it can be either excitatory (Szabadics et al, 2006) or inhibitory (Glickfeld et al, 2009). In addition, the three perisomatic interneuron groups are active at different times and show different firing patterns during network oscillations in vivo (Klausberger et al, 2003;Klausberger et al, 2005;Tukker et al, 2007;Lasztóczi et al, 2011;Lapray et al, 2012;Tukker et al, 2013) and also in in vitro preparations Hájos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%